COMMUNICATIVE INDICATORS OF IMPROVING THE QUALITY OF ENGLISH LANGUAGE TEACHING - Rashidova Gulshod Zarifovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article comprehensively explores the communicative indicators for enhancing English language teaching quality and elaborates on utilizing program tools to equip learners with English-specific communicative competencies.